Promoting the Physical Activity of Older Adults in Institutional Long‐Term Care: A Mixed‐Method Case Study - Narsakka, Noora; Suhonen, Riitta; Finskas, Johanna; Stolt, Minna (Wiley, 2026)
Introduction: Older adults living in institutional long-term care benefit from engaging in physical activity adapted to their functioning. Despite evidence of solutions to promote physical activity, recurrent evidence shows that older adults spend their time sedentary. More in-depth knowledge is needed about the current state of promoting the physical activity of older adults in institutional long-term care for improved practice in the future. We aimed to increase the understanding of older adults' physical activity promotion in institutional long-term care by investigating how, how much and by whom older adults' physical activity is promoted.
Methods: This is a concurrent mixed-method case study using data from a larger research project performed in an institutional, full-time, long-term care unit in Finland. Thirteen older adults and 12 staff members participated. Data were collected through focus groups, interviews, patient record transcripts and actigraphy between May and October 2023. A mixed-method analysis was conducted using the framework 'Following a thread'. Separate analyses of datasets were conducted, including analyses of qualitative and quantitative data using reflexive thematic analysis and descriptive statistics. Analytical questions were identified and further explored using all datasets to synthesise findings.
Results: Four themes were developed: (1) lack of physical activity, (2) plans for physical activity promotion, (3) nurses' role in activity promotion and (4) accessibility and freedom of movement.
Conclusion: Current activity promotion is not sufficient for older adults to achieve the benefits of physical activity for their health and functioning. Improvements are needed in delivering sufficient physical activities. Nurses' role in activity promotion should be developed to include care-integrated activities, spontaneous and organised activities and instrumental activities of daily living for older adults. Interprofessional work to promote activity could be used more. Stimulating elements in the physical environment and increasing freedom of movement could produce improvements in physical activity. Improvements in activity promotion can potentially be achieved with simple strategies and low additional costs.